The Variation of Spodic Characteristics in North Central Wisconsin - Knuteson, James A. (University of Wisconsin-Stevens Point, 1979)
Eleven sites were sampled along a south to north transect of north central Wisconsin. Samples were analyzed for spodic properties in selected subhorizons. Cation exchange capacity and pyrophosphate extractable iron and aluminum was found to increase along the transect. None of' the samples qualified as spodic horizons with the current chemical criteria. Several samples were identified as spodic horizons by morphological and micromorphological criteria. Changes are suggested for the limits of the chemical differentiating criteria. Relaxing the sesquioxide to clay ratio to 0.05 would help some Wisconsin spodosols meet the chemical criteria. Cautions are issued for the use of micromorphological differentia in identifying spodic horizons.